Pertanggungjawaban Korporasi Dalam Tindak Pidana Korupsi Pengadaan Barang Dan Jasa Pemerintah Di Bidang Konstruksi - Russel Butarbutar (Universitas Jayabaya, 2015)
Offenses of corruption and crime that often occurs in the procurement of goods/services that are common construction in accordance with Act No. 31 of 1999 such is: a crime against the state financial harm to the law or abuse of power, bribery offense group, group evasion offense in the post, extortion offense in office, deeds offense, offense relating to an interest in the procurement, and gratification. That the Corporation could be required for Corporate Responsibilities when the corruption in the procurement of goods and services in the field of construction that we can see at verdict No. 04/Pid. Sus/2011/PT. BJM which have permanent legal force (inkrachtvan gewische). The above findings generated through normative research methods to approach the analysis of legal materials, either primary, ie Act No. 31 of 1999 jo . Act No. 20 of 2001 on Eradication of Corruption, secondary legal materials, and tertiary legal materials.